2006
DOI: 10.1136/jmg.2006.043687
|View full text |Cite
|
Sign up to set email alerts
|

A molecular and clinical study of Larsen syndrome caused by mutations in FLNB

Abstract: The clinical signs most frequently associated with a FLNB mutation are the presence of supernumerary carpal and tarsal bones and short, broad, spatulate distal phalanges, particularly of the thumb. All individuals with Larsen syndrome-associated FLNB mutations are heterozygous for either missense or small inframe deletions. Three mutations are recurrent, with one mutation, 5071G-->A, observed in 6 of 20 subjects. The distribution of mutations within the FLNB gene is non-random, with clusters of mutations leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
121
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(131 citation statements)
references
References 54 publications
7
121
1
2
Order By: Relevance
“…Spatulate fingers were described in all cases of the initial paper by Larsen et al [16] and in 19 of 20 cases (95%) of Larsen syndrome with FLNB mutations reported by Bicknell et al [3]. Another hand anomaly, an accessory distal thumb phalanx, recently was reported in a patient with Larsen syndrome and a specific mutation in FLNB, but outside the calponin homology domain, causing the amino acid substitution G1691S [1].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Spatulate fingers were described in all cases of the initial paper by Larsen et al [16] and in 19 of 20 cases (95%) of Larsen syndrome with FLNB mutations reported by Bicknell et al [3]. Another hand anomaly, an accessory distal thumb phalanx, recently was reported in a patient with Larsen syndrome and a specific mutation in FLNB, but outside the calponin homology domain, causing the amino acid substitution G1691S [1].…”
Section: Discussionmentioning
confidence: 87%
“…Compared with five other patients with Larsen syndrome with mutations in the calponin homology domain [3], our patient had similar facial and spinal deformities but lacked the characteristic hand deformities (spatulate fingers) typically seen in this patient population (Table 1). Spatulate fingers were described in all cases of the initial paper by Larsen et al [16] and in 19 of 20 cases (95%) of Larsen syndrome with FLNB mutations reported by Bicknell et al [3].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Genetically, Larsen syndrome is primarily inherited through an autosomal dominant mode of transmission and associated with mutations in the Filamin B (FLNB) gene (8). Mapped to chromosome 3p14, Filamin B is a cytoskeletal protein that plays an important role in actin polymerization and signal transduction pathways that help control and guide proper skeletal development (9).…”
Section: Abstract: Carpal Bones; Larsen Syndrome; Supernumerarymentioning
confidence: 99%
“…It may also manifest with several hand anomalies, which may be of relevance to the hand surgeon. These include long cylindricalshaped fingers, spatula-shaped thumbs, short metacarpals and supernumerary carpal bones (8). Cervical kyphosis is the most serious manifestation of Larsen syndrome, predisposing patients to potentially life-threatening paralysis.…”
mentioning
confidence: 99%